2018
DOI: 10.1016/j.sjbs.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of serotype group B Streptococci neonatal infections associated with interleukin-6 level as a sensitive parameter for the early diagnosis

Abstract: Group B streptococcal infection (Streptococcus agalactiae) is one of the leading causes of life-threatening disease in the early neonatal period, resulting in sepsis, pneumonia, and meningitis. During invasive infections, an excessive release of pro-inflammatory cytokine, such as interleukin-6 (IL-6), thus IL-6 gene is significant, as a diagnostic marker of systemic infection of the newborns. The present study aimed to describe the epidemiology diagnostic of GBS disease in neonatal by phenotypic and genotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other risk factors reported are obesity, diabetes, advanced maternal age, and black ethnicity [22,23]. Numerous studies have also demonstrated a higher incidence of GBS colonisation in neonates born to mothers over the age of 30 [24][25][26]. At the opposite an Italian cohort study shows non-statistically significant excesses noted in pregnant women with term births, those aged over 30 years, Italians, pregnant women residing in rural areas within the province, and multiparous women and GBS colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors reported are obesity, diabetes, advanced maternal age, and black ethnicity [22,23]. Numerous studies have also demonstrated a higher incidence of GBS colonisation in neonates born to mothers over the age of 30 [24][25][26]. At the opposite an Italian cohort study shows non-statistically significant excesses noted in pregnant women with term births, those aged over 30 years, Italians, pregnant women residing in rural areas within the province, and multiparous women and GBS colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal sepsis and bacterial meningitis, immune responses associated with secretion of various cytokines are involved in the pathology, affecting disease severity and mortality (Barichello et al 2013;Machado et al 2014). Several studies have reported that serum TNF-α, IL-1β, IL-6, and IL-10 levels are elevated in GBS infection (Hashimoto et al 1999;Al Hazzani et al 2018), whereas serum IL-1α and CSF IL-6 levels are elevated in GBS meningitis (Fida et al 2006;Takahashi et al 2014). In severe neonatal sepsis, the serum IL-10 level is significantly higher (39.7 vs. 13.2 pg/mL) than the levels in non-severe sepsis, whereas neonates who died or developed severe sequela presented significantly high levels of GM-CSF (80.7 vs. 53.6 pg/mL, respectively) compared with those in individuals who were healthy when discharged (Leal et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of pneumonia in the pediatric population can be classified by age-specific versus pathogen-specific organisms (Rudan et al, 2013). Neonates are at risk from bacterial pathogens present in the birth canal, and this includes organisms such as group B streptococci, Klebsiella sp., Escherichia coli (Al Hazzani et al, 2018;Arif, 2018;Chen et al, 2019). S. pneumoniae, S. pyogenes, and S. aureus can be identified in late-onset neonatal pneumonia (Arif, 2018;Ebeledike & Ahmad, 2020).…”
Section: Inroductionmentioning
confidence: 99%